2019
DOI: 10.1039/c8tc05391j
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of high performance printed flexible conductors by doping of polyaniline nanomaterials into silver paste

Abstract: An innovation application of doping conjugated polyaniline nano-dendrites (PANIs) into electrical conductive composites (ECCs) to prepare advanced flexible or stretchable printing circuits with better electrical conductivity and mechanical stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…For the conduction mechanism, the addition of conductive PANIs nanomaterials is equivalent to providing more contact points for conductive composites. In our previous research [38,43], we found that there was a strong interaction between PANIs and silver flakes, which could alter the distribution of the silver flakes in the resins and enhance the tunneling state between them.…”
Section: Resultsmentioning
confidence: 99%
“…For the conduction mechanism, the addition of conductive PANIs nanomaterials is equivalent to providing more contact points for conductive composites. In our previous research [38,43], we found that there was a strong interaction between PANIs and silver flakes, which could alter the distribution of the silver flakes in the resins and enhance the tunneling state between them.…”
Section: Resultsmentioning
confidence: 99%
“…[100] In general, there have two types to control organicinorganic interface: surface functionalization [101][102][103][104][105][106][107][108][109][110] and addition of additives. [109][110][111][112][113] Surface functionalization of inorganic materials with organic molecules has been well-developed in the solution-based synthesis of nanostructured inorganic materials, including thiol chemistry on metal surfaces, [101] silane chemistry on oxide surfaces, [102] creating functional groups on metals and oxides by plasma exposure and ozone treatment, [103,104] radical formation and subsequent surface adsorption, [105][106][107] coating with charged small molecules, [108] surface wrapping or adsorption by long polymer chains, [114] etc. Due to the poor miscibility of the nanomaterials with the polymer matrix or the polymer solution, design of the functional groups on the nanomaterial surface has been focused on increasing the compatibility with the polymer.…”
Section: Electrospun Nanofiber Interfacesmentioning
confidence: 99%
“…Various interfacial designs to increase the stretchability of the Ag flake composites have been reported. [110][111][112][113][114]119,120] Jin et al fabricated Ag flake composite embedding electrospun poly(vinylidene fluoride) (PVDF) nanofibers (Figure 10a). [114] The pores with average size of 2.9 µm among the nanofibers were filled with the Ag-rich conductive composite, resulting in high electrical conductivity of 9900 S cm −1 .…”
Section: Metal Interfaces For Conductive Stretchable Compositesmentioning
confidence: 99%
“…In order to fulfill these aims, we propose a hybrid approach for e-fabric skin by combining screen printing and heat transfer techniques. The design of the e-fabric-like skin is based on the structure of multi-line capacitors with two main layers, which are composed of SWCNT/stretchable silver paste [27][28][29][30][31][32] as electrode layers and special-structure fabrics as a dielectric layer. The resulting e-fabric-skin has high flexibility, is breathable, lightweight, and has easy integration into clothing.…”
Section: Introductionmentioning
confidence: 99%